2022
DOI: 10.1111/tbed.14675
|View full text |Cite
|
Sign up to set email alerts
|

A review of estimated transmission parameters for the spread of avian influenza viruses

Abstract: Avian influenza poses an increasing problem in Europe and around the world. Simulation models are a useful tool to predict the spatiotemporal risk of avian influenza spread and evaluate appropriate control actions. To develop realistic simulation models, valid transmission parameters are critical. Here, we reviewed published estimates of the basic reproduction number (R0), the latent period and the infectious period by virus type, pathogenicity, species, study type and poultry flock unit. We found a large vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…We simulated the following scenarios, using the estimates described above: (1) turkeys with LPAI; (2) turkeys with HPAI; (3) chickens with LPAI; (4) chickens with HPAI; (5) chickens with H5N1; (6) chickens with H5N2; and for H7; (7) chickens with H7N1; (8) chickens with H7N3; and (9) chickens with H7N7 (summarized in Figures 2 and 3). For scenarios with chickens and H5N2, H7N3 and H7N7, no estimates for the period of latency were available (Kirkeby & Ward, 2022), and the default fixed latency period of 1 day was used in these simulations. The predicted numbers of infected birds, days of peak infection and days of disease fadeout for each scenario are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We simulated the following scenarios, using the estimates described above: (1) turkeys with LPAI; (2) turkeys with HPAI; (3) chickens with LPAI; (4) chickens with HPAI; (5) chickens with H5N1; (6) chickens with H5N2; and for H7; (7) chickens with H7N1; (8) chickens with H7N3; and (9) chickens with H7N7 (summarized in Figures 2 and 3). For scenarios with chickens and H5N2, H7N3 and H7N7, no estimates for the period of latency were available (Kirkeby & Ward, 2022), and the default fixed latency period of 1 day was used in these simulations. The predicted numbers of infected birds, days of peak infection and days of disease fadeout for each scenario are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Estimates for the transmission rate (β), latency and duration of infection were obtained from the data cited in a previous study (Kirkeby & Ward, 2022). We only included estimates from experiments in which the numbers of animals and the 95% CI for each of the variables were reported.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, previous efforts have demonstrated that Anatidae are competent vectors for avian influenza due to their high shedding rates [31,32], long duration of infection [33,34], and comparatively high prevalence in the wild [35,36]. However, while previous studies have provided us with valuable information on the general response to infection for Anseriformes, the importance of these species to the transmission of AIVs both across space [30,37] and across the wild waterfowl – domestic poultry interface [18,38] suggests that future work with these species could aim to develop better estimates of parameters needed for transmission risk modeling [39] such as minimum infectious dose which is currently only rarely included [40,41]. Similarly, the continued high representation of Anatidae in mortality events and surveillance sampling [20] emphasizes the importance of studies focused on including emerging viral strains to inform possible outcomes prior to outbreak events and to maintain current data.…”
Section: Discussionmentioning
confidence: 99%
“…Reviews conducted so far on avian influenza have focused on virological and clinical aspects [ 24 , 25 ] or on risk factors [ 26 28 ], including transmission routes [ 29 , 30 ]. Two recent studies reviewed transmission parameter values based on experimental studies [ 31 ] and on both experimental and field studies [ 32 ], but to the best of our knowledge no comprehensive analysis of mechanistic models has been undertaken. To fill this gap, we conducted a systematic review of mechanistic models applied to avian influenza in poultry to (i) describe the mechanistic models used and their epidemiological context, (ii) list AIV transmission parameters, and (iii) provide insights on avian influenza transmission and the impact of control measures.…”
Section: Introductionmentioning
confidence: 99%